Superscan on 18F-FDG PET-CT imaging for lymphoma: how frequent is it? - Qureshi, Pir Abdul Ahad Aziz; Aleem, Javaria; Niazi, Dr. Imran Khalid; Hassan, Aamna; Bashir, Humayun (Journal of the Pakistan Medical Association, 2022)
This retrospective study was conducted to evaluate the frequency of PET superscan in baseline staging scans of lymphoma patients.Thestudy was conducted at theShaukat Khanum Memorial Cancer Hospital, Lahore, from October 1, 2018 to August 31, 2019. A retrospective review of baseline PET-CT scans of 203 lymphoma patients, performed during the period of October 1, 2017 to August31,2018, was done from the institutional database. Out of these 203 patients, PET superscan pattern was observed in 13 (6.4%) patients, 08 (61.5%) males and 05 (38.5%) females. Eight (61.5%) patients had Non-Hodgkin’s lymphoma, while 05 (38.5%)had Hodgkin’s lymphoma. Based on TNM staging 10 (76.9%) patients had stage IV disease, 01 (07.6%) had stage IIIS disease, and 2 (15.4%) had stage II disease. PET-CT superscan pattern is uncommon and is not dependent on the stage of the disease. It should be recognised in clinical practice as it suggests a poor prognosis. Keywords: PET-CTScan, Lymphoma, 18F-FDG.